Factors influencing consumers’ choices of oral hygiene products: A cross-sectional study - Awais, Faiza; Shahzad, Hazik Bin; Naheed, Kiran; Khan, Ayyaz Ali (UI Scholars Hub, 2019)
Background: Environment, peer-groups, and salespersons influence consumers’ purchasing decisions regarding oral hygiene products. Other influences include various cultural, social, demographic, and socioeconomic factors. This study was designed to determine factors motivating and influencing consumers while choosing oral hygiene aids. Methods: 410 patients (age, 10–70 years), who visited the outpatient department of Sheikh Zayed Medical Complex, Lahore, Pakistan, were subjected to a close-ended questionnaire survey. Factors investigated included cost, packaging, media advertisement, perceptions, and previous experiences. Results: The cost of oral-hygiene products (82%) were the biggest influence. Advertisements influenced 55% of consumers in their purchase decisions regarding oral hygiene products. Reason for product use was disease prevention (58.7%) and freshness of breath (31%). Logistically, females were significantly 0.66 times less likely to be affected by media advertisements. Low income and occupations were 2.27 times more likely to be influenced by advertisements. Price was not significant meaning all categories were influenced by price equally. Conclusion: Consumers’ choices of oral hygiene products were influenced by information available through mass media and the products’ cost-effectiveness. Dentists should be aware of these influences and should accordingly advise their patients considering their needs and influencing factors.